The effect of educational games on students’ speaking skills - Mareta, Selly; Arifin, Samsul; Sari, Dwi Rosita (Universitas PGRI Madiun, 2024)
Speaking skills are essential for students in junior high school as they learn English as a second language. The ability to speak in English not only improves academic performance but also prepares students for future academic and professional endeavors. A supportive and deep learning environment and innovative teaching methodologies can help students overcome these obstacles and build confidence in their English ability over time, like an educational game. This research aims to determine the effect of student speaking skills in educational games such as guessing games. This research was conducted in one of the state junior high schools in Madiun. Two classes, namely control and experiment, consisting of 25 students, are compared. The control class is taught using an educational method, and the experimental class uses educational games called guessing games. The researcher used a random sampling technique and quantitative research to analyze the data with the t-test. The result of this research is that educational games' guessing games affect students who are taught with guessing games; the students who are taught with guessing games have a better score than those taught with conventional technique. The teacher should make an innovative learning process with guessing games to increase student speaking skills.